Retinal and optic nerve microvasculature assessment in nephritic and nonnephritic systemic lupus erythematosus: a comparative analysis - Esraa; Mahmoud El-Mayah; Basma M.S Mahmoud; Magda S Abdelaziz; Mohamed S. Kotb (Delta Journal of Ophthalmology)
Background Lupus nephritis is considered one of the most common complications of systemic lupus erythematosus (SLE) that greatly affects the overall prognosis. Retinopathy, as one of the disease complications, is an indicator of disease severity, frequent renal impairment, and poor prognosis. Therefore, screening of subclinical retinopathy is of great importance as retinopathy and nephropathy are somehow associated in SLE patients.